Pengaruh Manajemen Aset Terhadap Efektivitas Pengelolaan Aset Tetap Pemerintah Daerah - Sisca, Yulia; Sarwani, Sarwani; Adriani, Ade (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study was conducted to determine the influence of asset management on the effectiveness of fixed asset management through the variables of fixed asset inventory, legal audit, fixed asset valuation, fixed asset optimization, and supervision and control of fixed assets. This type of research is quantitative, using purposive sampling techniques, which are limited to certain individuals who can provide the desired information and who understand and are able to provide a complete picture of fixed asset management. The unit of analysis in this research is all working units managing regional government property in 38 (thirty-eight) Regional Apparatus Organizations (SOPD) within the Province of Central Kalimantan. The working unit managing BMD will be represented by individual BMD officials, namely the User Asset Manager in each SOPD and the Head of the SOPD as the Asset User, with a total of 76 respondents. Data collection techniques utilize questionnaires, and data analysis uses multiple linear regression analysis with the analysis tool used being IBM SPSS version 25. The results of the study indicate that the variables of fixed asset inventory, fixed asset valuation, fixed asset optimization, and supervision and control of fixed assets have a negative and significant effect on the effectiveness of fixed asset management, while the legal audit variable has a positive and significant effect on the effectiveness of fixed asset management.